Toward understanding the kinetics of disassembly of ferritins of varying origin and subunit composition. (August 2022) - Krausova, Katerina; Charousova, Marketa; Kratochvil, Zdenek; Takacsova, Paulina; Tesarova, Barbora; Sivak, Ladislav; Peskova, Marie Kudlickova; Sukupova, Martina; Zivotska, Hana; Makovicky, Pavol; Yamashita, Ichiro; Okamoto, Naofumi; et al.
Highlights: Reversible reassembly properties of four different types of ferritins were studied. For all examined ferritins, disassembly is faster in acidic pH than in basic pH. Archaeal Pfu ferritin is the most stable in both, acidic and basic conditions. All ferritins form protein corona hampering their cellular uptake. For all ferritins, kidney/liver are the preferential bioaccumulation sites. Abstract: Understanding the reversible reassembly properties of ferritins (FRTs) is crucial for enabling their applicability in nanomedicine. These properties include drug loading capabilities and also subsequent payload release in desired site-of-action. Thus, the presented study is focused on understanding the disassembly of recombinantly produced FRTs of varying origin and subunit composition, i.e . equine FRT composed of 22 L - and 2 H -subunits (EcaLH) or 24 L -subunits (EcaL), human FRT composed of 24 H -subunits (HsaH) and archaeal Pyrococcus furiosus FRT (Pfu). Disassembly was distinctly influenced by pH and ionic strength. Except for Pfu, the disassembly kinetics in acidic pH is rapid upon reaching an innate threshold, reaching the final state within minutes. Disassembly kinetics in basic pH is slower. Pfu is partially disassembled within the entire pH range. While equine FRT disassembles into free subunits, HsaH disassembles into subunit clusters. EcaL and Pfu form large aggregates during disassembly in mildly acidic pH, although basic pH causes partial disassembly without aggregation, suggesting usability for basic pH-triggered drug loading. We show that in human serum/plasma, FRTs readily form protein corona, hampering their uptake. Interestingly, we found out that archaeal Pfu likely exhibits similar receptor affinity as mammalian FRTs. Further, in vivo toxicity and biodistribution study of a single dose of FRTs demonstrated very low toxicity of FRTs and their preferential liver/kidney bioaccumulation. Graphical abstract: Image, graphical abstract